The Role Parents Beginning Writing Learning as An Effort to Support Learning Primary School - Lelianasari; Damaianti, Vismaia S (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
In early elementary school classes, during initial writing learning, students face various difficulties, for example, recognizing letters, forming words, and constructing coherent sentences. This research uses a qualitative phenomenological design approach. The research was based on primary data from five parents of grade 1 elementary school students. The data collection techniques used were interviews, observation, and documentation. The data analysis technique used is Milles and Huberman (reduction, presentation, and verification). Data credibility testing was also carried out through data source triangulation. Research findings show that the key to the success of students' initial writing learning is the role of parents at home. Parental support so that students are enthusiastic about learning is by providing stationery, study space, agreed study hours, and giving more appreciation. Parents direct students to form more lines and draw when learning to write. Then, when students learn to write letters, parents use checkerboard books so that the morphology of the letters and the distance between the letters are consistent. Students are instructed by their parents to write down the names of objects at home. Parents' main focus is to foster students' learning motivation by paying attention to students' self-confidence in learning to write.